Situational Positioning: A Grounded Theory of Registered Nurse Decision-making in Western Australian Nursing Homes - Scott, Beverley Margaret (Curtin University, 2003)
This grounded theory study investigated how registered nurses (RNs) managed problem-solving and decision-making in residential aged care facilities (nursing homes) in Western Australia. The outcome of the study was the substantive theory of situational positioning, the process used by the RN participants when they were trying to get things right .In-depth interviews were conducted with 25 purposefully selected registered nurses and nursing home management staff. The interviews were transcribed verbatim, and analysed using the constant comparative method. Other sources of data. guided by theoretical sampling. were selected documents such as government reports regarding aged care, and some field observations. Situational positioning was a process that involved physical. cognitive, emotional, and moral dimensions, and reflected how the RN participants acted and responded when dealing with situations at work. Situational positioning was conceptualised as occurring along two intersecting continua of behaviours, and these behaviours emerged from the data as four interrelated categories. Yielding and confronting represented the poles on a continuum of action-oriented behaviour, with being flexible and being rigid on a continuum that reflected more affective or attitudinal responses. The four categories that made up the positioning continua had both positive and negative meanings in relation to the actions and responses of the participants, depending on the particular situation. Yielding was a conceptual category that reflected participants' comments about stopping a particular action and trying something else or giving up completely and even leaving the situation. f he term confronting was used to describe participants' actions that were based on assertiveness that was seen as a constructive behaviour, or anger that tended to be non-productive.Being flexible meant that the participants were responsive to changing situational variables, and this was usually seen as a desirable attribute of effective nursing practice in aged care. However, it could also mean being pliant and ready to compromise in order to get through situations when the participants realised that they would be unable to get things right. At the other end of the response axis, the term being rigid was defined as the opposite of being flexible, that is, having firmly fixed or set ways of responding. or a tendency to respond to situations in the same way in all circumstances. The basic psychosocial problem, being unable to get things right, had two properties. One property was temporal, in that the problem occurred when the participants were getting behind or running late because of having insufficient time. usually due to interruptions. The second property of the problem was more qualitative in that contextual and intervening conditions led the participants to feel that they were not doing things properly because of adverse conditions. Conditions that varied .situational positioning were those that led to the participants being unable to get things right, such as having insufficient time. working with unqualified carers. and trying to meet the differing expectations of various stakeholders. Situations that were easy for the participants to manage involved known routines and few, if any. interruptions. In those circumstances, si uational positioning was intuitive and the phases of recognising, prioritizing, and moving on were negotiated quickly. In more complex situations, or when significant interruptions occurred, the participants followed an alternative pathway, which involved recognising that something in the situation changed. then compromising. that is. choosing a new course of action.Compromising required tolerance, as the participants adjusted their expectations of what could be achieved in the circumstances. Repositioning then occurred belore they moved on to the next task or to the end of their shifts. Moving on. the third phase in the process, involved persevering as they continued trying to get things right. The adverse conditions that prevailed in nursing homes during the time of this study impeded nursing practice and the delivery of consistently good standards of care for all residents. Situational positioning enabled the participants to persevere in their efforts to try to get things right, but their capacity to maintain the effort was eroded by the apparently unrelenting nature of the adverse conditions that existed in nursing homes. The main conclusion of this study was that the RN role in nursing homes in Western Australia was ill-defined, and inefficient in terms of best utilisation of nursing time. Recommendations included a review of the RN role in aged care and implementation of strategies that would enable aged care RNs to focus on their clinical roles.